Civil Rights Protests and Election Outcomes: Exploring the Effects of the Poor People's Campaign - D. Mark Anderson; Kerwin Kofi Charles; Krzysztof Karbownik; Daniel I. Rees; Camila Steffens (Institute of Labor Economics (IZA), 2023)
The Poor People's Campaign (PPC) of 1968 was focused on highlighting, and ultimately reducing, poverty in the United States. As part of the campaign, protestors from across the country were transported to Washington, D.C. in 6 separate bus caravans, each of which made stops en route to rest, recruit, and hold non-violent protests. Using data from 1960-1970, we estimate the effects of these protests on congressional election outcomes. In the South, we find that PPC protests led to reductions in Democratic vote share and turnout, while in the West they may have benefited Democratic candidates at the expense of their Republican rivals.
Keywords: D72; I30; J15; N32; 330; Poor People's Campaign; election outcomes; voting behavior; protests; race